Managing large-volume literature searches in research synthesis studies. - Havill, Nancy L.; Leeman, Jennifer; Shaw-Kokot, Julia; Knafl, Kathleen; Crandell, Jamie; Sandelowski, Margarete (Nursing Outlook)
Abstract: Background: Systematic reviews typically require searching for, retrieving, and screening a large volume of literature, yet little guidance is available on how to manage this volume. Purpose: We detail methods used to search for and manage the yield of relevant citations for a mixed-methods, mixed research synthesis study focused on the intersection between family life and childhood chronic physical conditions. Methods: We designed inclusive search strings and searched nine bibliographic databases to identify relevant research regardless of methodological origin. We customized searches to individual databases, developed work-arounds for transferring large volumes of citations and eliminating duplicate citations using reference management software, and used this software as a portal to select citations for inclusion or exclusion. We identified 67,555 citations, retrieved and screened 3,617 reports, and selected 800 reports for inclusion. Discussion/Conclusions: Systematic reviews require search procedures to allow consistent and comprehensive approaches and the ability to work around technical obstacles.